Citrates of mineral substances in the technological process of manufacturing bakery products - Shevchenko, Anastasiia; Galenko, Oleg (My University, 2021)
The study of the complex effect of sugar substitute — fructose and citrates of calcium, magnesium, zinc, iron, both individually and in a mixture, on the manufacturing process of bakery products and the properties of semi-finished and finished products was provided. The course of the processes in the dough was characterized by the kinetics of sugars during the maturation of the dough, the properties of the water-flour suspension using amylograph, the springy-elastic properties of the dough were studied using farinograph.
Keywords: mineral substances; diabetes; bakery product; quality; fructose; кафедра технології хлібопекарських і кондитерських виробів; кафедра технології м’яса і м’ясних продуктів